การใช้คอมพิวเตอร์ช่วยกำหนดขนาดของแสลบเพื่อการผลิตเหล็กแผ่นรีดร้อน - ขวัญประชา บุญกว้าง (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The objective of the thesis is to develop a computer system that assists in issuing specifications of dimensions of slabs that will be purchased for the production of hot-rolled steel plates. In the system, the sizes, and the number of each size, of the plates are given by customers. Production processes and conditions set by the customers and the suppliers are also considered in the system. The research has studied the requirements and constraints of the customers, the slab suppliers, and the hot-rolled steel plates producers. It has designed a decision-making process and developed a program that assists in specifying the dimensions and the numbers of the slabs required. The procedure of the developed system starts from entering the procurement constraints by the user. Then, the computer will calculate all possible production process plans and will eliminate unsuitable ones. After that, the user will assign priorities and the computer will specify the most suitable dimensions and quantities of the required stabs. The test of the system with the case study finds that the time to make decision is reduced by 11.43 to 29.7% and the yield is improved by 3.35 to 3.47%.